ADMINISTRASI PENDIDIKAN BERBASIS TEKNOLOGI INFORMASI SEBAGAI UPAYA PENINGKATAN KUALITAS LAYANAN PEMBELAJARAN PAI - Laila Aliyatu Muthoharoh (CV JK Riset Publishing Group, 2026)
This research is motivated by the low quality of Islamic Religious Education (PAI) learning services due to administrative management that is still manual and conventional. The purpose of this study is to analyze the implementation of information technology-based educational administration in improving the quality of PAI learning services in schools. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews, observations, and documentation of school principals, PAI teachers, and administrative staff. The results show that the integration of school management information systems significantly improves administrative efficiency, data accuracy, and responsiveness of PAI learning services. The use of digital platforms facilitates coordination among educational stakeholders. The conclusion of the study confirms that IT-based educational administration is a strategic solution in improving the quality of PAI learning services in a sustainable manner.